Modelling of solar distillation system with phase change material storage medium - Al-Hamadani A.A.F.; Shukla S.K. (My University, 2025)
An experimental investigation on a passive solar still with myristic acid as phase change material is carried out to examine the effect of both the mass of phase change material and basin water on the daily distillate output and efficiency of the system under indoor simulated condition. Basic energy balance equations are written to predict the water and glass temperatures, daily distillate output and instantaneous efficiency of the single slope solar distillation system with phase change material. It is found that the higher mass of phase change material with lower mass of water in the solar still basin significantly increases the daily yield and efficiency, but when the amount of phase change material exceeds 20 kg productivity reduces. Therefore, a novel and simple of solar stills with phase change material is proposed to enhance the overall productivity of the distillation system. The new solar still has increased the distillate output by 35-40%. The use of inner glass cover temperature for productivity prediction has also been investigated, and the prediction shows relatively better agreement with the experimental data.